Development of an Information Exchange Model for supporting logistics operations. (16th April 2009) - Lau, H.C.W.; Ho, G.T.S.; Tang, C.X.H.; Tse, Y.K.; , E.N.H. Cheng
In this rapidly changing and volatile world, the fast flow of information plays an important role in achieving a reliable physical flow of logistics operations. With logistics information systems, the exchange of data is necessary to provide the support of cross-functional logistics activities. Different parties and systems pass the data back-and-forth and have to work together to accomplish the logistics activities and operations. For example, to obtain advice from the Decision Support Systems, the order processing systems retrieve the data and then export it to the report and output systems. However, these systems were designed individually and are not able to exchange and share data with each other efficiently. This paper proposes an Information Exchange Model and industry process information exchange standard to provide the capability to share and exchange data between logistics systems.